2016
DOI: 10.1016/j.redox.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The novel triterpenoid RTA 408 protects human retinal pigment epithelial cells against H2O2-induced cell injury via NF-E2-related factor 2 (Nrf2) activation

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…We hypothesized that upregulation of NRF2 and NRF2 driven antioxidant enzymes might be part of the protective mechanism induced by AβPP overexpression in MC. Consistent with our work and this hypothesis, recent studies have reported that: 1) NRF2-deficient mice develop AMD-like retinal pathology with photoreceptor loss [52]; 2) upregulation and activation of NRF2 protect RPE cells [53] and photoreceptors [54,55] against oxidative stress in in vitro and in vivo models of retinal degeneration; 3) pharmacological activation of NRF2 inhibited gliosis of MC in an in vivo model of retinal degeneration and increased NRF2 responsive antioxidants in cultured MC [56]. Interestingly, several studies also showed pivotal role for NRF2 in the brain astrocytes.…”
Section: Aβpp Induced the Er-associated Degradation Of Misfolded Protsupporting
confidence: 92%
“…We hypothesized that upregulation of NRF2 and NRF2 driven antioxidant enzymes might be part of the protective mechanism induced by AβPP overexpression in MC. Consistent with our work and this hypothesis, recent studies have reported that: 1) NRF2-deficient mice develop AMD-like retinal pathology with photoreceptor loss [52]; 2) upregulation and activation of NRF2 protect RPE cells [53] and photoreceptors [54,55] against oxidative stress in in vitro and in vivo models of retinal degeneration; 3) pharmacological activation of NRF2 inhibited gliosis of MC in an in vivo model of retinal degeneration and increased NRF2 responsive antioxidants in cultured MC [56]. Interestingly, several studies also showed pivotal role for NRF2 in the brain astrocytes.…”
Section: Aβpp Induced the Er-associated Degradation Of Misfolded Protsupporting
confidence: 92%
“…Nrf2 is activated when cells are exposed to oxidative stress. To date, a wide variety of Nrf2 activators have been reported [10] , [11] , [12] , [13] . Among them, a highly effective novel triterpenoid, RS9, was recently isolated as an Nrf2-specific activator [12] , [14] .…”
Section: Introductionmentioning
confidence: 99%
“… 11 13 Along these lines, pretreatment with omaveloxolone also protects retinal pigment epithelial cells from oxidative destruction via activation of Nrf2. 14 Based on in vitro and animal studies, omaveloxolone exhibited high protein binding with extensive tissue distribution, making it a suitable potential oncologic agent.…”
Section: Introductionmentioning
confidence: 99%